FARMERS’ AWARENESS CONCERNING THE INFLUENCE AND MANAGEMENT OF CLIMATIC CHANGES ON ENVIRONMENTAL ECONOMY AND CROPS NUTRITIONAL STATUS - Vladia Mara ARNĂUTU; Cristian IEDERAN; Marcel DÎRJA; Petru BURDUHOS; Dragoș OROIAN; Antonia ODAGIU (Scientific papers series "management, economic engineering in agriculture and rural development", 2025)
In our days, climate changes are globally recognized as one of the most challenging pressures on agriculture. They may have consequences not only on crop yields, but on the whole agrifood sector. A survey was conducted on 383 subjects, which own farms and confront with possible extreme phenomana as consequences of climatic changes. The questionnaires were distributed in rural areas of Bistrița-Năsăud County in autumn and early winter of 2024. The aim of our scientific approach was to identify the farmers’perceptions on the existence of climatic changes, and their particular effects on agriculture sector. The raw data were statistically processed using basic statistics and multivariate analyzis. Simple Spearman correlation between variables were established, and factorial analyzis through its component PCA (Principal Components Analysis) was implemented for emphasizing the main factors affecting the farmers awareness on climatic changes and their effects with which they may confront. The results of our study show that only part of the questioned farmers are fully aware of the presence of climatic changes, and of their effects on soil nutritional status, water availability, or productivity. This suggests the importance of implementing training programs targeted to support farmers to improve their knowledges in the field.